Adapting clinical skills volunteer patient recruitment and retention during COVID-19 - Nazerali-Maitland, Alasdair; Holden, Reed; Jones, Amanda; Uitto Cardoso, Jenni; Levido, Kelly; Douglas, Christina (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2021)
Implication Statement: Institutions have been faced with the unique challenge of continuing to deliver medical education to students in a COVID-19 environment.1,2 Clinical skills teaching must be adapted to the pandemic environment, which begins with retaining Volunteer Patient (VP) engagement to facilitate the development of students’ patient care aptitudes. The number of available VPs has been significantly reduced by the pandemic. We propose actionable solutions to recruit, engage, and retain VPs that can be easily adopted at any site. The SLIM-COVID framework can assist programs in altering curricula to deliver clinical skills with patient involvement in a pandemic environment.